Democratic Leadership Model of Young Kiai (Lora) at Islamic Boarding School in Madura - Nurdin, Arbain; Ishomuddin, Ishomuddin; Faridi, Faridi (J-MPI (Jurnal Manajemen Pendidikan Islam), 2024)
Kiai plays such a central role in Islamic boarding school. The fame of Islamic boarding school cannot be separated from the role of kiai, and not all descendants of kiai are able to replace his position. The purpose of this study is to analyze the leadership patterns of young kiai at Sabilul Muttaqien Islamic Boarding School in Pamekasan Madura and analyze the supporting and inhibiting factors. This research uses a qualitative approach with unstructured interview techniques and non-participant observation techniques in collecting data and testing it with source triangulation and method triangulation techniques. While the research subjects are kiai, students and the community. The study in this research is a study that is not widely described in previous studies because this study focuses more on the leadership model of young kiai in Islamic boarding schools. The results showed that the leadership pattern of young kiai at Sabilul Muttaqien Islamic Boarding School in Pamekasan is democratic. The supporting factors for his leadership are the persistence of young kiai and the support and trust of the community. While the lack of experience is a factor inhibiting his leadership.